(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The Curriculum and Assessment Policy Statement (CAPS) of 2012 focuses on certain aspects of the social upheaval the US experienced during the 1960s and 1970s. Under the heading of “Civil society protests of the 1950s to the 1970s”, grade 12 learners examine the American Civil Rights and Black Power movements, the Women’s movement, and the various peace movements, of that period. However, most South African educators and students are unfamiliar with another, similar movement of the same time period, the American Indian people’s movement for civil rights. Some familiarity with this movement and its historical background may offer the classroom teacher an opportunity for the enrichment of historical study and learning. Knowledge of this movement can provide a broader context for the topics specified by CAPS. The history of the Native American peoples is often neglected in the study of US history. Just as the history of the African people of South Africa has become central to a complete understanding of the development of this country, so a renaissance in the study of American Indian history has become important in history teaching and learning in the United States. In particular American race relations issues are better understood in a context of black-white Indian issues than in terms of a simple black-white bi-polarity. Furthermore, such awareness introduces the possibility for conducting comparative historical analysis in the South African classroom. This paper first establishes the historical background of 19th century white-Indian relations. This was a period of intermittent warfare, followed by treaty-making and the confinement of Indian people to reservations. From the 1880s onward, these reservations were all but destroyed by new government policy through the Dawes Act. The 20th century was a period of changed and changing government policy toward the Indian population. The Indian Reorganization Act of 1934 partially revived Indian tribal life. However, after the Second World War, further damage to tribal life was caused by the policy of the termination of relations between the government and the tribes. This led to the growing militancy of Indian response, in the 1960s and 1970s. The American Indian Movement (AIM) and other Indian organisations confronted the state and Federal governments, in Indian country and beyond, on reservations and in the US Supreme Court. These confrontations (from the late 1950s to the early 1970s) precisely coincide with the time period specified in CAPS. By the end of this period, the American public image of the Indian peoples had begun to change and a general awareness of Indian problems and issues began to express itself.